Internally Guided Lower Limb Movement Recruits Compensatory Cerebellar Activity in People With Parkinson's Disease - Drucker, Jonathan H.; Sathian, K.; Crosson, Bruce; Krishnamurthy, Venkatagiri; McGregor, Keith M.; Bozzorg, Ariyana; Gopinath, Kaundinya; Krishnamurthy, Lisa C.; Wolf, Steven L.; Hart, Ariel R.; Evatt, Marian; Corcos, Daniel M.; et al. (Frontiers in Neurology, 2019)
Background: Externally guided (EG) and internally guided (IG) movements are postulated to recruit two parallel neural circuits, in which motor cortical neurons interact with either the cerebellum or striatum via distinct thalamic nuclei. Research suggests EG movements rely more heavily on the cerebello-thalamo-cortical circuit, whereas IG movements rely more on the striato-pallido-thalamo-cortical circuit.1 Because Parkinson’s (PD) involves striatal dysfunction, individuals with PD have difficulty generating IG movements.2 Objectives: We hypothesized individuals with PD would employ a compensatory strategy favoring the cerebellum over the striatum during IG lower limb movements. Methods: 22 older adults with mild-moderate PD, who had abstained at least 12 hours from anti-PD medications, and 19 age-matched controls performed EG and IG rhythmic foot-tapping during functional magnetic resonance imaging. Participants with PD tapped with their right (more affected) foot. External guidance was paced by a researcher tapping participants’ ipsilateral 3rd metacarpal in a pattern with .5s to 1s intervals, while internal guidance was based on pre-scan training in the same pattern. BOLD activation was compared between tasks (EG vs. IG) and groups (PD vs. control). Results: Both groups recruited the putamen and cerebellar regions. The PD group demonstrated less activation in the striatum and motor cortex than controls. A task (EG vs. IG) by group (PD vs. control) interaction was observed in the cerebellum. Conclusions. These findings support the hypothesized compensatory shift in which the dysfunctional striatum is assisted by the less affected cerebellum to accomplish lower limb movement in individuals with mild-moderate PD. These findings are of relevance for postural control disorders and freezing of gait problems frequently noted in many people with PD.